Headlights on the prairie : essays on home - Rebein, Robert, 1964- (University Press of Kansas, 2017)
"In his third book, Robert Rebein pulls together a unified collection of narrative essays set largely on the high plains of western Kansas. He introduces readers to a world of feedlot cowboys, stock car drivers, and young boys dreaming of basketball glory, while also providing glimpses into a darker side: damaged young men returning home from war, long-haul truckers addicted to crystal meth, the sadly heroic residents of a nursing home bearing the euphemistic name Manor of the Plains. Each chapter tells its own story, while each story advances the overarching narrative of a native son growing up in, leaving, and ultimately returning to the place that formed him as a writer and a person"--